Sate Kajang Hj Samuri / Nurul Aim Amirah Sofian ... [et al.] - Sofian, Nurul Aim Amirah; Azmi, Nurzakirah; Syed Monudeen Khan, Sarifah Adila; Wan Saghir, Wan Nor Ain Nasriq; Bainal, Roslan (2019)
Sate Kajang is a company that sell satay for over than two decades. It is a company that is established by Hj Samuri and his five children. Throughout the years of selling satay, their company have achieved many achievements and been given the title of "Good Manufacturing Practice" and halal certificate from JAKIM. They are trusted by many consumers. They also have evolved from not only selling satay, but also other products from frozen burger patties and also 'popia'. They also follow the trends of selling online and delivered to customer's doorstep in order to sustain and maintain in the business. Their latest achievement is to be able to export their products to outside of Malaysia.